Jet morphology analysis of microwave‐generated plasma for microfabrication of optics. Issue 12 (5th August 2022) - Dong, Yuqing; Zhang, Jiacheng; Zhang, Peng; Tian, Hengxi; Yu, Deping
Abstract: The jet morphology of the fluorine‐containing plasma is important for the accuracy and efficiency of nondestructive optical fabrication. This paper investigated changes in the jet size and active radicals of microwave plasma. Results show that little addition of CF4 and O2 in Ar could promote the ionization process, but excessive addition of them would inhibit the production of active radicals and limit the jet size. Both optimizing the proportion of CF4 and O2 and the applied power can greatly improve the jet morphology. The regulation principle of the plasma jet morphology was interpreted as the balance between the ionization resistance of the working gas and the applied power, which ensures a high etch rate and process resolution. Abstract : By analyzing the changes in the jet size and active radicals of the fluorine‐containing plasma jet, this paper proposed a morphology regulation mechanism of the plasma jet used for etching processing of optic components, that could provide the regulation direction for adjusting the work parameters to meet different processing requirements.